CAPITAL INTENSITY AS DETERMINANT OF TAX AVOIDANCE IN IDX BUMN20 COMPANIES: INSIGHTS FROM 2023 - Suryadi, Teguh; Astama, Silvia Putri; Gani, Firman (LPPM Universitas Putera Batam, 2025)
This study investigates the impact of capital intensity on tax avoidance in 20 companies listed in the IDX BUMN20 index on the Indonesia Stock Exchange in 2023. Using simple linear regression, the results show a significant effect capital intensity on tax avoidance. This suggests that companies with higher capital intensity are more likely to engage in tax avoidance strategies, such as asset depreciation and tax incentives. Furthermore, 74% of the variation in tax avoidance is explained by capital intensity. These findings highlight the importance of fixed asset investment on corporate tax behavior and the need for regular evaluations of tax policies.